TRANSFORMASI MINYAK JELANTAH MENJADI PRODUK EKONOMIS MELALUI PROGRAM PEMBERDAYAAN MASYARAKAT DI RW 05 PAKINTELAN GUNUNGPATI - Widiarti, Nuni; Lestari, Devy; Sulistyaningsih, Triastuti; Astuti, Budi; Rohmah, Rojaa Maysa; Muna, Nala Izzul; Maylani, Amanda Farizka (Universitas Padjadjaran, 2026)
Used cooking oil is household waste that is often not managed properly, giving it the potential to pollute the environment and endanger human health. Reusing it without proper procedures and disposing of it carelessly can lead to soil and water pollution and increase the risk of degenerative diseases. This community service activity aims to empower the residents of RW 05, Pakintelan Village, Gunungpati District, Semarang City, through training on the utilization of used cooking oil into environmentally friendly, value-added products, namely soap, aromatherapy candles, and briquettes made from biomass waste. The program was carried out using a participatory and educational approach through the stages of counseling, technical training, practical assistance, and simple evaluation. The activity, which took place on May 25, 2025, was attended by 40 active PKK members and facilitated by a team of lecturers from the Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Semarang. The results of the activity showed that participants were able to produce the products independently and apply appropriate technology-based household waste recycling techniques. As a form of sustainability, the residents replicated the soap and candle products to participate in the HATINYA PKK competition at the village level, where they won third place. This activity proves that community empowerment based on waste management can promote ecological awareness, practical skills, and family economic independence. The program has great potential to be replicated in other communities with similar social and environmental characteristics, especially in urban and semi-urban areas facing similar household waste management problems. Minyak goreng bekas (jelantah) merupakan limbah rumah tangga yang sering kali tidak dikelola dengan baik, sehingga berpotensi mencemari lingkungan dan membahayakan kesehatan. Penggunaan ulang tanpa prosedur yang tepat serta pembuangan sembarangan dapat menimbulkan pencemaran tanah dan air serta meningkatkan risiko penyakit degeneratif. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memberdayakan warga RW 05 Kelurahan Pakintelan, Kecamatan Gunungpati, Kota Semarang melalui pelatihan pemanfaatan minyak jelantah menjadi produk ramah lingkungan yang bernilai ekonomi, yaitu sabun, lilin aromaterapi, dan briket dari limbah biomassa. Program dilaksanakan secara partisipatif-edukatif melalui tahapan penyuluhan, pelatihan teknis, pendampingan praktik, dan evaluasi sederhana. Kegiatan yang berlangsung pada 25 Mei 2025 ini diikuti oleh 40 anggota aktif PKK dan difasilitasi oleh tim dosen FMIPA Universitas Negeri Semarang. Hasil kegiatan menunjukkan bahwa peserta mampu menghasilkan produk secara mandiri serta mempraktikkan teknik daur ulang limbah rumah tangga berbasis teknologi tepat guna. Sebagai wujud keberlanjutan, warga mereplikasi produk sabun dan lilin untuk mengikuti lomba HATINYA PKK tingkat kelurahan dan meraih juara 3. Kegiatan ini membuktikan bahwa pemberdayaan masyarakat berbasis pengelolaan limbah dapat mendorong kesadaran ekologis, keterampilan praktis, serta kemandirian ekonomi keluarga. Program ini memiliki potensi besar untuk direplikasi di komunitas lain dengan karakteristik sosial dan lingkungan serupa, terutama di kawasan urban dan semi-urban yang menghadapi persoalan serupa terkait limbah rumah tangga.